Concept of Asaya, Kostha and Kosthanga (Splanchnology) in Ayurveda (AYUSHDHARA, 2022)
The basic knowledge of an organ system is necessary to know the etio-pathogenesis, management and maintenance of health of an individual. Splanchnology is the study of visceral organs, which includes digestive, urinary, reproductive and respiratory systems, situated in the thoraco-abdominal-pelvic cavity. Concept of organs systems are highlighted in Ayurveda with three terminologies viz. Asaya, Kostha, Kothanga. Asaya is mentioned as Aadhisthana and Riktasthana which means cavities and blank spaces for lodging certain anato-physiological elements. They are 7 in numbers viz. Vatasaya, Pittasaya, Shlesmasaya, Raktasaya, Amasya, Pakwasaya, Mutrasaya and the Garbhasaya which are present in the thoracico-abdominal-pelvic cavity. Mahasrota, Sariramadhya and Mahanimna are the words mentioned in relation with Kostha which can be understood as gastro intestinal tract, middle part of the body and the pelvic cavity. Nabhi, Hridaya, Kloma, Yakrita, Pleeha, Vrikka, Vasti, Purishadhara, Amasaya, Pakwasaya, Uttaraguda, Adharaguda, Kshudranata, Sthulantara and Vapavahana are the Kosthangas which are interrelated organs of gastrointestinal tract and cardiovascular system, present in cavities of the middle part of the body. The hollow muscular organs and the structures present in thoraco-abdominal-pelvic cavity are collectively considered as Asaya, Kostha and Kosthangas. Therefore these 3 terminologies can be incorporated with splanchnology in modern science. In this work we tried to analyse the concept of splanchnology in Ayurveda in terms of Asaya, Kostha, Kosthanga. This will be helpful for better understanding and study of the topic in a single platform, and gives the glimpse of the morpho-physiological aspect of visceral organs mentioned in Ayurveda in a nutshell.